The Efforts of SMA Negeri 10 Palembang in Shaping the Characteristics of Students Through the Application of Embracing Pancasila Values - Ulfa, Ulfa (LPPM Institut Studi Islam Sunan Doe, 2022)
This study aims to find out how the efforts of SMAN 10 Palembang in shaping the character of students through the implementation of Pancasila values as an Indonesian human identity. This research is a type of qualitative research and the method used is the case study method. Data collection techniques used observation and documentation. The results of observations that have been made show that SMAN 10 Palembang has implemented Pancasila values well. This can be seen from the attitudes and actions of students in carrying out their daily activities at school. Through the appreciation of Pancasila values, the attitudes and actions of students who are obedient in worship, help each other, love the motherland, respect the opinions of others and carry out their obligations well as students are formed.